2020
DOI: 10.3389/fendo.2020.599255
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Hyponatremia and Hypernatremia in COVID-19 Pneumonia. A HOPE-COVID-19 (Health Outcome Predictive Evaluation for COVID-19) Registry Analysis

Abstract: Dysnatremia is associated with increased mortality in patients with community-acquired pneumonia. SARS-COV2 (Severe-acute-respiratory syndrome caused by Coronavirus-type 2) pneumonia can be fatal. The aim of this study was to ascertain whether admittance dysnatremia is associated with mortality, sepsis, or intensive therapy (IT) in patients hospitalized with SARS-COV2 pneumonia. This is a retrospective study of the HOPE-COVID-19 registry, with data collected from January 1th through April 31th, 2020. We select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
107
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(149 citation statements)
references
References 36 publications
17
107
1
5
Order By: Relevance
“…Indirect stimulation of IL-6 is mediated by an injury to the alveolar basement membrane, resulting in activation of hypoxic pulmonary vasoconstriction pathway that lead ADH release61 (17).On the contrary, IHD was signi cantly associated with hyponatremia than hypernatremia. This association is also reported in HOPE -COVID-19 registry (16) In our population, sodium metabolism was affected by the complications of covid-19 infection, like AKI and TEE. We found that, the patients who had AKI developed hypernatremia 5.5 times more as compared to those who did not have AKI.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Indirect stimulation of IL-6 is mediated by an injury to the alveolar basement membrane, resulting in activation of hypoxic pulmonary vasoconstriction pathway that lead ADH release61 (17).On the contrary, IHD was signi cantly associated with hyponatremia than hypernatremia. This association is also reported in HOPE -COVID-19 registry (16) In our population, sodium metabolism was affected by the complications of covid-19 infection, like AKI and TEE. We found that, the patients who had AKI developed hypernatremia 5.5 times more as compared to those who did not have AKI.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, hypertension was signi cantly associated with hypernatremia, although hyponatremia was also common but didn't reach to a signi cant level. Ruiz and Cuesta in HOPE-COVID-19 registry analysis also found signi cant association of hypernatremia in hypertensive patients, the mechanism of this nding is not evident and it will need further evaluation (16). The hyponatremia on the other hand is also reportedly associated with covid hypertensive patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Hypernatraemia is a common laboratory abnormality in COVID-19 patients, found in 3,7% of patients hospitalised due to COVID-19 in the HOPE registry [9]. Similarly to hyponatraemia, increased plasma sodium levels are an adverse prognostic factor in non-COVID patients although this awaits confirmation in COVID-19 series.…”
Section: Management Of Hypernatraemia In Covid-19mentioning
confidence: 99%
“…A number of case reports describing hyponatraemia of various etiologies was initially published [4][5][6][7]. Later, a descriptive study of 16 patients with COVID-19-related hospitalization found 50% of them had hyponatraemia [8], whereas the HOPE study, an international registry of 4664 hospitalized COVID-19 patients, found that 20.5% and 3.7% had hyponatraemia and hypernatraemia, respectively [9]: both hyponatraemia and hypernatraemia were generally mild (130-134 mEq/l in 16.7%), severe hyponatraemia (<120 mEq/l) was found only in 0.4%. Multivariable logistic regression analysis showed that male sex and age > 70 years were independently associated with hyponatraemia at admission, whereas smoking, tachypnea and serum creatinine >1.5 mg/dl bore a positive, independent association with admission hypernatraemia.…”
mentioning
confidence: 99%